Fresno County Bar Association and Fresno County Women Lawyers Joint Luncheon with Betty Medsger - Watkins, Howard::::::::: (1986)
Betty Medsger talking with Tomar Mason; Mary Louise Frampton in background Hilton coffee pot on table